Economic Development and Changing Women Lives: Evidence from Women Employment Participation in India - Bhat, Suhail Ahmad; Mallniah, L.C.; Singh, Shambhavi (International Socioeconomic Review, 2024)
This paper examines the trends and patterns of women employment in India with the use of NSSO data from 1984 to 2011-12 and the latest PLFS data from 2017-2022. The paper draws out the changes in female employment during the period 1984-2022 by using exploratory research methods. The pa-per analyses the temporal trends from 1984 to 2022 across rural and urban areas and presents an overview of the status of female employment in India. The results show that over the period of last ten years the women employment in India has increased with manifold. The employment opportunities of women are showing an increasing trend with a shifted patterns of employment from agriculture sector to territory sector. The WPR of rural women of 15 years and above has increased to 35.8 percent. Whereas, among the urban female, it has been increased to 21.9 percent Moreover, the Indian economy is also witnessing the women entrepreneurship development in the country. Results shows that the unemployment rate (in percent) in usual status (ps+ss) among rural women has declined from 3.8 percent in 2017-18 to 1.8 in 2022-23. Whereas, among the urban female it has declined from 10.8 percent to 7.5 percent in the recall period. Therefore, the present paper attempts to analyze the economic development and the changing women employment participation in both organized and unorganized sector in India.